The evolution of σγP with coherence length. (11th July 2016) - Caldwell, Allen
Abstract: Assuming the form σ γ P ∝ l λ eff at fixed Q 2 for the behavior of the virtual-photon proton scattering cross section, where l is the coherence length of the photon fluctuations, it is seen that the extrapolated values of σ γ P for different Q 2 cross for l ≈ 10 8 fm. It is argued that this behavior is not physical, and that the behavior of the cross sections must change before this coherence length l is reached. This could set the scale for the onset of saturation of the parton densities in the photon, and thereby saturation of parton densities in general.